Exploring Employee Status Change as a Career Shock: Leadership and Motivation Affect on Employee Engagement - Tomi Murtomo; Agus Arijanto (Journal of Sustainable Economic and Business, 2026)
Objectives: This study aims to examine the impact of transformational leadership and public service motivation on employee engagement among KPK employees following the disruptive event of transitioning employment status to civil state apparatus. Methodology: A quantitative causal associative study with a sample of 301 people from 1.157 KPK employees affected by the employment status change and who were still working at KPK at the time of the research. Data was obtained from Google Form questionnaire distributed via e-mail to respondents. Quantitative analysis used Partial Least Square and causal relationships were explored using Structural Equation Modeling (SEM) through the SmartPLS version 4 application. Finding: The transition of employment status as a positive valenced career shock most strongly influences employee engagement. Transformational leadership does not significantly affect employee engagement. However, its influence on employee engagement becomes more effective and significant when moderated by career shock. Meanwhile, the significant influence of public service motivation on employee engagement is not affected by the moderation of career shock. Conclusion: This study demonstrates that transformational leadership does not always significantly influence employee engagement, particularly in public institutions, but intervention from other variables is required to enhance its effectiveness.